Student interactions with ethical issues in the lab: results from a qualitative study - Kelly Laas; Christine Z Miller; Eric M Brey; Elisabeth Hildt (Research Ethics Review)
Student researchers encounter ethical issues daily, but little is known about their unique perspectives. This article presents the results of 30 qualitative semi-structured interviews exploring students’ views and experiences around ethical issues in research groups. During the interviews, students were asked to describe challenges and successes they have encountered in their lab, their conception of what counts as an “ethical issue in research,” and how they handle these issues when they arise. Against this background, the article discusses students’ conceptions of ethical issues in research environments, the types of issues students reported facing, how these issues were ultimately resolved, and finally, the factors, internal qualities, and lessons learned that help students thrive in research environments, as well as some of the challenges students face – especially international students. Many of the ethical challenges interviewees discussed focused on interpersonal issues, highlighting the intense collaboration most graduate students have with their colleagues and supervisors. Findings from this study point to the need for targeted training programs for students and faculty supervisors focusing on building mentoring relationships and finding space in the lab where open communication can occur around ethical research practices.